Heart Rate Variability Biofeedback and Psychotherapy in Polycystic Ovary Syndrome: Description of a Case Report to Shed Light on this Understudied Condition - Pruneti, Carlo; Guidotti, Sara; Cosentino, Chiara (Clinical Journal of Obstetrics and Gynecology, 2023)
Background: Although there is minimal information on the role of stress in PCOS, it is well-known that it may trigger the exacerbation and maintenance of the disease. Despite there being only a few studies in the literature, many researchers highlighted situations of autonomic hyperactivation characterizing PCOS. In light of these assumptions, the purpose of this study is to report on a patient who underwent psychological intervention to enhance stress management skills. Case: A 30-year-old woman was referred by the endocrinologist. From a clinical-psychological point of view, the condition of the patient was characterized by a modest psychophysiological activation. Interpersonal difficulties did not allow the patient to benefit from the social support of her loved ones, further favoring the maintenance of the excessive arousal generated by stressful life events. The patient was treated with HRV-Biofeedback integrated within cognitive-behavioral psychotherapy. Discussion: The multidimensional intervention brought benefits to the patient, teaching her better stress management strategies (i.e., reduction of psychological symptoms and improvement of hormonal tests). Keeping in mind the interplay between physiological, psychological, and interpersonal factors is fundamental in all psycho-somatic and somato-psychic disorders and is crucial to enhance the use of specific treatments to restore psychophysical well-being.